Customer Satisfaction Index (CSI) sebagai Alat Ukur Kepuasan Peserta BPJS Ketenagakerjaan Cabang Bandung Suci - Gustomo, Sheva Roga; Asri, Melati Dewi; Ravenska, Nanda; Kurniawan, Iwan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to measure participant satisfaction with the services provided at the Bandung Suci Branch Office of BPJS Ketenagakerjaan and to formulate recommendations for service improvement. The research employed a descriptive quantitative method, with primary data collected through questionnaires distributed to 107 participants, complemented by field observations. The analysis was conducted using the Customer Satisfaction Index (CSI) approach with five indicators of customer satisfaction proposed by Kotler and Keller, namely product quality, service quality, emotional conditions, price, and cost. The findings indicate that participant satisfaction falls into the “fairly satisfied” category, with a CSI score of 61.82%. The lowest-performing dimensions include responsiveness, cost, empathy, reliability, product quality, and assurance. These results highlight the need for improvements, particularly in service speed and efficiency. As a follow-up, the study recommends a redesigned queuing system at the branch office to enhance service effectiveness and optimize participant satisfaction.